Static versus dynamic sitting modes when performing on-desk tasks amongst preschool children. - Alperovitch-Najenson, Deborah; Lifshits, Tal; Wilk, Ortal; Ezra, David; Amichai, Taly; Kalichman, Leonid (Work, 2025)
Background: Studying at school and engaging in social activities are primarily performed while sitting, contributing to a sedentary lifestyle, which poses a major health concern for adults and children. Sitting independently and being stable facilitates success in reaching and connecting with objects. Objective: Recognizing the potential negative consequences of SB, this study explored the effect of using a fit ball as an alternative seating option in classrooms to reduce sedentary behavior. Methods: We employed a repeated-measures design to compare the fine motor accuracy of 37 preschool children (18 boys and 19 girls, aged 4–6 years with a mean age of 5.48 ± 0.54 years) when seated on standard chairs versus fit balls. The children were assessed through six subtests designed to evaluate fine motor accuracy appropriate for their age group. Results: Our findings revealed no significant difference in fine motor accuracy between the two seating modes (p > 0.05), indicating that using a fit ball as a seating alternative does not compromise the fine motor skills of preschool children. Furthermore, no clear preference for either seating mode among the children was detected (Z = −1.79, p = 0.074). Conclusion: While using fit balls may not enhance fine motor accuracy, they could still be considered an alternative seating in classrooms to reduce sedentary behavior without negatively impacting fine motor development. Such seating arrangements, including dynamic chairs or fit balls, could foster the development of healthy habits without adversely affecting academic skills. Further research may explore other benefits of dynamic seating and its long-term effects on child development.